Midazolam exposure in the paediatric intensive care unit predicts acute post-traumatic stress symptoms in children. Issue 4 (July 2022) - Long, Debbie; Gibbons, Kristen; Le Brocque, Robyne; Schults, Jessica A.; Kenardy, Justin; Dow, Belinda
Abstract: Background: Clinically significant post-traumatic stress symptoms (PTSS) have been reported in up to a quarter of paediatric intensive care unit (PICU) survivors. Ongoing PTSS negatively impacts children's psychological development and physical recovery. However, few data regarding associations between potentially modifiable PICU treatment factors, such as analgosedatives and invasive procedures, and children's PTSS have been reported. Objectives: We sought to investigate the medical treatment factors associated with children's PTSS after PICU discharge. Methods: A prospective longitudinal cohort study was conducted in two Australian tertiary referral PICUs. Children aged 2-16 y admitted to the PICU between June 2008 and January 2011 for >8 h and <28 d were eligible for participation. Biometric and clinical data were obtained from medical records. Parents reported their child's PTSS using the Trauma Symptom Checklist for Young Children at 1, 3, 6, and 12 months after discharge. Logistic regression was used to assess potential associations between medical treatment and PTSS. Results: A total of 265 children and their parents participated in the study. In the 12-month period following PICU discharge, 24% of children exhibited clinically elevated PTSS. Median risk of death (Paediatric Index of Mortality 2 [PIM2]) score was significantly higher in the PTSS group (0.31 [IQR 0.14–1.09] v 0.67 [IQR 0.20–1.18]; p = 0.014). Intubation and PICU and hospital length of stay were also significantly associated with PTSS at 1 month, as were midazolam, propofol, and morphine. After controlling for gender, reason for admission, and PIM2 score, only midazolam was significantly and independently associated with PTSS and only at 1 month (adjusted odds ration (aOR) 3.63, 95% CI 1.18, 11.12, p = 0.024). No significant relationship was observed between the use of medications and PTSS after 1 month. Conclusions: Elevated PTSS were evident in one quarter (24%) of children during the 12 months after PICU discharge. One month after discharge, elevated PTSS were most likely to occur in children who had received midazolam therapy.